Authentic Assessment Of Hinduism Learning In Elementary School - Sudarsana, I Ketut (Institut Hindu Dharma Negeri Denpasar, 2021)
The purpose of this study was to describe the authentic assessment of Hinduism learning in elementary school. Assessment is an integral part of learning as a whole. The position of assessment in the design of learning implementation is part of the three main components of implementation, namely learning objectives, learning activities, and assessment of learning outcomes. Learning activities are designed to meet the learning objectives that must be achieved. Assessment is needed to determine the level of success and achievement of learning objectives. Assessment is also used as feedback for the learning process itself. Assessment is needed so that corrective actions can be taken in the learning process. One of the characteristics of a good assessment is sustainable so that improvements in the learning process can be performed continuously.